A flaw was detected in the formula: $f(n) = f(q_{i} \times m') = f(m') \times \frac{q_{i}^{a_{i} + 2} - 1}{q_{i}^{a_{i} + 2} - q_{i}}$ where $m' = \frac{n}{q_{i}}$. This error was fixed by the another formula: $f(n \times N_{m}) = f(q_{i}^{2} \times m') = f(m') \times \frac{q_{i}^{a_{i} + 2} - 1}{q_{i}^{a_{i} + 2} - q_{i}}$ where $N_{m} = \prod_{i = 1}^{m} q_{i}$ is the primorial number of order $m$. The other parts of the proof remain the same...

We continue using the reductio ad absurdum as the principal argument, but this time we made the proof shorter. We changed the abstract and the content of the paper in this new version.